2008
DOI: 10.1210/jc.2007-2672
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Basal Metabolic Rate and Physical Activity Contribute to Hypothalamic Obesity

Abstract: Energy expenditure, rather than energy intake, has a greater role in the development of obesity after cranial tumor therapy. Reductions in BMR and physical activity, leading to a positive energy balance and weight gain despite an age-appropriate calorie intake, may contribute to hypothalamic obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 27 publications
2
42
0
3
Order By: Relevance
“…Maximal ability to utilize oxygen during exercise (VO 2 max ) depends on cardiac output, arterial oxygen content, and muscle oxygen extraction (31). In two recent studies, basal metabolic rate adjusted to total body weight was significantly lower in adult subjects with CP compared with controls (32), as well as in children with hypothalamic obesity (including CP) compared with simple obese controls (33). As basal metabolic rate is highly correlated with FFM and muscle mass, these findings could be in agreement with ours and suggest an alteration in muscle function, both at rest and during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Maximal ability to utilize oxygen during exercise (VO 2 max ) depends on cardiac output, arterial oxygen content, and muscle oxygen extraction (31). In two recent studies, basal metabolic rate adjusted to total body weight was significantly lower in adult subjects with CP compared with controls (32), as well as in children with hypothalamic obesity (including CP) compared with simple obese controls (33). As basal metabolic rate is highly correlated with FFM and muscle mass, these findings could be in agreement with ours and suggest an alteration in muscle function, both at rest and during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not clear whether hypothalamic obesity occurs as a result of decreased energy expenditure or increased energy intake, recent studies have demonstrated that a decreased basal metabolic rate and lack of physical activity contribute to the development of overweight and obesity [42, 43]. A previous study showed that cranial irradiation induces hypothalamic obesity in a dose-dependent manner and is associated with insulin hypersecretion in the developing brain [44].…”
Section: Discussionmentioning
confidence: 99%
“…Host metabolic factors such as reduced energy expenditure [37], increased fat mass, [38], increased insulin resistance and hyperinsulinemia [39], and metabolic syndrome [39] may also be responsible for this late-onset variability and increase in BMI in groups 2 and 3.…”
Section: Discussionmentioning
confidence: 99%